KONSEP DASAR SUPERVISI PENDIDIKAN: IMPLIKASI TERHADAP PENGEMBANGAN KINERJA GURU - Puji Rosianna Sinaga; Nopesari Samosir; Valdo Hutauruk; Chindy Nababan; Evinti Nadeak; Abai Manupak Tambunanf (CV. Denasya Smart Publisher, 2024)
Educational supervision plays a crucial role in enhancing the quality of education within schools. This research aims to delve deeper into the fundamental concepts, principles, techniques, and approaches of educational supervision through a comprehensive literature review. The methodology employed involves a thorough examination, analysis, and synthesis of various scholarly sources pertaining to educational supervision. The findings highlight that educational supervision is a deliberate process aimed at providing professional support to educators, thereby fostering improvements in the teaching-learning process and outcomes. The foundational principles underlying this practice include scientific, collaborative, constructive, realistic, progressive, innovative, reflective, and secure approaches. Various techniques can be utilized, including both individual and group supervision. Among these, clinical supervision emerges as an effective approach, comprising stages such as initial meetings, observation, analysis, and feedback sessions between supervisors and educators. In summary, the effective implementation of educational supervision necessitates a systematic understanding and application by all stakeholders within schools, ultimately contributing to the advancement of teacher professionalism and the overall quality of education.